(untitled) (Linguostylistic Studies, 2022)
The works by Liubov Ponomarenko, a modern Ukrainian writer, are quite original and written in a brightly talented manner. They are called “a blue miracle of the Ukrainian short stories” and are characterized by the mosaic of images, mystery of the plot, presence of the fantastic elements, imitation of the “whimsical prose” traditions, laconism/brevity and dominance of the subjective attitude to the objectivity of the depicted things. The fact that these stories can be treated as neo-impressionistic ones can significantly affect the perception of the writer’s language. However, the linguistic and stylistic features of her short prose, in particular, the variety of the epithet constructions are still understudied. This determines the relevance of the research. The purpose of the article is to identify the semantic, grammatical, functional and stylistic features of the epithets in the short prose by Liubov Ponomarenko. The material for the research involves the epithet constructions (more than 500 examples of their contextual use), collected from 13 short stories by the writer. The study findings argue that the author uses epithet constructions of all possible varieties: adjectival, participial, adverbial and substantive ones. Traditionally, the first two types are the most used, but the author also makes extensive use of the adverbial epithets and noun constructions. The study has also revealed that the nouns in such structures can be used not only in the genitive (genitive epithet) but in the accusative, instrumental and locative cases. Besides, the author uses in her own way uncoordinated attribute epithets in the locative case with a preposition. In general, the article states that the imagery of Liubov Ponomarenko’s prose canvas is created by the combination of epithet constructions of different nature. They help the writer to create holistic images of the heroes, to depict their surroundings and households, to display landscape etc.